Pituitary gonadotrophic hormone synthesis, secretion, subunit gene expression and cell structure in normal and follicle‐stimulating hormone β knockout, follicle‐stimulating hormone receptor knockout, luteinising hormone receptor knockout, hypogonadal and ovariectomised female mice - Abel, M; Widen, A; Kumar, T; Pakarinen, P; Huhtaniemi, I; Christian, H; Wang, X (John Wiley and Sons, Inc., 2014)
To investigate the relationship between gonadotroph function and ultrastructure, we have compared, in parallel in female mice, the effects of several different mutations that perturb the hypothalamic‐pituitary‐gonadal axis. Specifically, serum and pituitary gonadotrophin concentrations, gonadotrophin gene expression, gonadotroph structure and number were measured. Follicle‐stimulating hormone β knockout (FSHβKO), follicle‐stimulating hormone receptor knockout (FSHRKO), luteinising hormone receptor knockout (LuRKO), hypogonadal (hpg) and ovariectomised mice were compared with control wild‐type or heterozygote female mice. Serum levels of LH were elevated in FSHβKO and FSHRKO compared to heterozygote females, reflecting the likely decreased oestrogen production in KO females, as demonstrated by the threadlike uteri and acyclicity. As expected, there was no detectable FSH in the serum or pituitary and an absence of expression of the FSHβ subunit gene in FSHβKO mice. However, there was a significant increase in expression of the FSHβ and LHβ subunit genes in FSHRKO female mice. The morphology of FSHβKO and FSHRKO gonadotrophs was not significantly different from the control, except that secretory granules in FSHRKO gonadotrophs were larger in diameter. In LuRKO and ovariectomised mice, stimulation of LHβ and FSHβ mRNA, as well as serum protein concentrations, were reflected in subcellular changes in gonadotroph morphology, including more dilated rough endoplasmic reticula and fewer, larger secretory granules. In the gonadotophin‐releasing hormone deficient hpg mouse, gonadotrophin mRNA and protein levels were significantly lower than in control mice and gonadotrophs were correspondingly smaller with less abundant endoplasmic reticula and reduced numbers of secretory granules. In summary, major differences in pituitary content and serum concentrations of the gonadotrophins LH and FSH were found between control and mutant female mice. These changes were associated with changes in expression of the gonadotrophin subunit genes and were reflected in the cellular structure and secretory granule appearance within the gonadotroph cells.